The Role of Midwife in Community Empowerment About Early Detection of Pregnancy Complication in Proppo Public Health Center - Rusady, Yulia Paramita; Peristiowati, Yuly; Suhita, Byba Melda (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-